Pathogenesis Specifics of Allergic Reactivity in Hypertensive Conditions of Pregnants - Mukhamedkhanova Sh. T.1, Yuldasheva D.S.2, Mirzaev N.B.3, Ruzieva N.Kh.4, Aripova F.S.5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Significant allergic reactions and anaphylactic type cytotoxicity are registered in thepathogenesis of cell damage in pregnant women with hypertensive conditions. Determining role ofindirect mast cell degranulation and allergic changes in neutrophils during pregnancy that complicated bypreeclampsia, allows to identify the allergic status of the body, which is very importance for improvingthe quality of early diagnosis, treatment and prevention. The purpose of the study was to identify theallergic reactivity of pregnant women suffering from hypertensive disorders and to develop practicalrecommendations to improve the quality of early diagnosis.Materials and Method: We observed 6 group of participants: pregnant women with clear allergy clinic,uncomplicated preeclampsia, pregnant women with light stage of preeclampsia, latent sensitization, pregnantwomen with preeclampsia combined with clear allergy clinic, conditionally healthy pregnant women – 1stcontrol group, practically healthy non-pregnant women – 2nd control group, practically healthy men – 3rdcontrol group. Using non-infection allergens, we called different types of allergic reactions and conductedclinical and allergic examinations, general test of bleed, urine, feces, indirect mast cell degranulation testand neutrophil alteration test.Results: Within all control groups, the rate of positive reaction against the allergic agents made up less than10 percent. In all pregnant women with clear clinical picture of allergies complicated or uncomplicatedpreeclampsia, as well as in pregnant women with preeclampsia with latent sensibilization, mast celldegranulation indexes were 4.5-8.6 times higher than that of control group. Among 90 examined pregnantwomen, positive reactions of indirect mast cell degranulation were observed in 204 cases.Conclusion: In cell damage pathogenesis during preeclampsia, anaphylactic and cytotoxic type allergicreactions play important role. The positive reactions of indirect mast cell degranulation in pregnant womenwith an explicit allergy complicated by preeclampsia is significantly higher than in pregnant women withpreeclampsia with hidden sensitization.